Neuroimaging : a teaching file - Castillo, Mauricio (LWW Teaching File Series., 2015)
With 100 illustrated cases in print and an eBook containing the 100 print cases plus another200 cases, this volume in the Teaching File Series gives you ready access to actual cases culled from the teaching files of major medical centers. Neuroradiology: A Teaching File covers a wide variety of CNS diseases that are presented as unknowns with coverage of both brain and head and neck cases. Each case features two to four images and follows the Teaching File template: clinical history, findings, differential diagnosis, diagnosis, discussion, questions, key issues for the report, what the clinici.